2011
DOI: 10.3233/efi-2010-0903
|View full text |Cite
|
Sign up to set email alerts
|

Professional development of academic library professionals in Kerala

Abstract: The paper aims to bring out the problems and prospects of the professional development opportunities of academic library professionals in the Universities in Kerala. The study is a part of research undertaken to survey the professional development activities and educational needs of library professionals in the major Universities of Kerala because of the developments in Information communication technology. The study recommends methods for improving the knowledge/skills of library professionals. The aim of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…After learning new approaches and techniques, university library staff members carry out efficient services to meet organizational objectives. These results are similar to the findings of the researches conducted byAyob (2011);Deve & Shaik (2012);Bhatti & Nadeem (2014);Mathew et al (2011); Chen (2012), andAnasi &Ali (2014).Findings of the study revealed that university library professionals had a positive attitude towards professional development courses. They realized that adoption of user centered services was not at all possible without skilled and motivated staff.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…After learning new approaches and techniques, university library staff members carry out efficient services to meet organizational objectives. These results are similar to the findings of the researches conducted byAyob (2011);Deve & Shaik (2012);Bhatti & Nadeem (2014);Mathew et al (2011); Chen (2012), andAnasi &Ali (2014).Findings of the study revealed that university library professionals had a positive attitude towards professional development courses. They realized that adoption of user centered services was not at all possible without skilled and motivated staff.…”
supporting
confidence: 89%
“…Mahmood (2002) revealed that the future of academic librarians was not safe without learning new technology. Mathew et al (2011) mentioned that the technological changes had a positive impact on the attitudes of the library professionals regarding professional development. Chen (2012) concluded that information literacy courses as professional development directly influenced the attitude of library professionals and encourage them to provide valued services to the users.…”
Section: Attitude Of Library Professionals Towards Professional Devel...mentioning
confidence: 99%
“…Whether in the current iteration or future direction of the academic library, CPD for academic librarians should be seen as a necessity for the attainment of success and relevance. Mathew et al (2011) note that librarians engage in continuing education programmes for various reasons, including the need to acquire new skills, update their knowledge or basic education, get trained in the latest technologies, improve library services, train junior staff and improve relations with fellow professionals. In their literature review, Saleem and Ashiq (2020) observe that most of the efforts of CPD have been related to technical aspects, such as library automation, reference management software and searching techniques.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To meet the ever-changing demands of the users, library professional require continuously updated knowledge and skills for effective performance. Continuing education is necessary for every professional, not only in library profession but also in all service sectors and it is fundamentally a responsibility of the individual professional (Mathew, Baby & Pillai, 2011). Professional development is universally recognized in education and librarianship as imperative for on-going effectiveness.…”
Section: Introductionmentioning
confidence: 99%